The impact of malocclusion and its treatment on quality of life: a literature review - M. ZHANG, C. MCGRATH & U. HÄGG (Paediatric Dentistry, 2006)
The aim of this paper is to review the literature relating to the impact of malocclusion, and the treatment of malocclusion, on physical, social and psychological health (i.e. quality of life, QoL).